2018
DOI: 10.5539/ijbm.v13n7p157
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship Initiatives in Enhancing Creativity and Innovation

Abstract: The current study aimed at understanding the influence of the Entrepreneurship Initiatives on creativity and innovation in business. It was hypothesized that the dimensions of entrepreneurship including (Strategies, Technology, Resources, Management Support and Culture) positively influences the creativity and innovation of business within the Jordanian environment. The sample of the study was derived from a telecommunication company which included (34) individuals from the high and the middle management.The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…According to the study on the mediating potential of work engagement toward employee attitudes and outcomes by Hoque et al (2017), an individual’s intrinsic psychological connection allows employees to make use of their available corporate entrepreneurship characteristics to maximize intellectual property results. Ahmetoglu et al (2018) and Al Qudah (2018) also found that organizations with nurturing environments that encourage employees to work with an initiative mindset, creativity and innovation allow them to engage at work with more energy and are more dedicated to bringing innovation to an organization. Zehir et al (2012) also found that an entrepreneurial environment that stimulates innovation, risk propensity and proactiveness results in greater organizational commitment among employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the study on the mediating potential of work engagement toward employee attitudes and outcomes by Hoque et al (2017), an individual’s intrinsic psychological connection allows employees to make use of their available corporate entrepreneurship characteristics to maximize intellectual property results. Ahmetoglu et al (2018) and Al Qudah (2018) also found that organizations with nurturing environments that encourage employees to work with an initiative mindset, creativity and innovation allow them to engage at work with more energy and are more dedicated to bringing innovation to an organization. Zehir et al (2012) also found that an entrepreneurial environment that stimulates innovation, risk propensity and proactiveness results in greater organizational commitment among employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2006), to explore entrepreneurial possibilities that can expand economies (Ferriani et al. , 2020) and increase innovation (Al Qudah, 2018). Furthermore, it is suspected that cultivating a paradigm of positivity around ADHD pathology will reveal more ways to productively and progressively incorporate positive aspects of neurodiversity into society.…”
Section: Discussionmentioning
confidence: 99%
“…The authors encourage educators to acknowledge and nurture the neurological differences of individuals with ADHD in ways that cultivate the schema shown here to positively affect IJEBR 30,4 entrepreneurship. Doing so could inspire the population of individuals with ADHD, commonly regarded as deficient (Kessler et al, 2006), to explore entrepreneurial possibilities that can expand economies (Ferriani et al, 2020) and increase innovation (Al Qudah, 2018). Furthermore, it is suspected that cultivating a paradigm of positivity around ADHD pathology will reveal more ways to productively and progressively incorporate positive aspects of neurodiversity into society.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Innovation is the only common theme underlying all forms of corporate entrepreneurship and smart organization. Thus, it is a defensible and meaningful assertion based on the fact that smart organization characteristics and entrepreneurship are closely related to various types of innovations, including technological innovation (Al Qudah, 2018;Al Shobaki et al, 2018).…”
Section: De and Timentioning
confidence: 99%